Environmental Responsibility And Company Life Cycle On Cash Holding With Geographical Diversification As Moderation Variable - Mahwiyah, Mahwiyah; Suripto, Suripto; Rosini, Iin (SEAN Institute, 2024)
The research aims to determine the influence of environmental responsibility on geographic factors. Influence of the Life Cycle on Cash Holding. InfluenceEnvironmental Responsibility influences Cash Holding and Diversification Geographic Factors. Life Cycle Influences Cash Holding and Diversification Geographic Factors on industrial companies listed on the Indonesia Stock Exchange. This research uses secondary data from the company's annual financial reports. This type of research is associative quantitative. The number of samples in this research was 50 companies. During the five years of observation 2018-2022, there were 243 observation data. To test the hypothesis, this research uses panel data regression. Based on the test results, the environmental responsibility variable affects Cash Holding. Based on the test results, the Life Cycle variable does not affect Cash Holding. The influence of Environmental Responsibility does not affect Cash Holding and Geographic Factor Diversification. Based on the test results, the Life Cycle does not affect Cash Holding and Geographic Factor Diversification